2007
DOI: 10.1007/s00066-007-1588-2
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Radiotherapy for Prostate Cancer

Abstract: Postprostatectomy RT can be recommended with FB due to an improved CTV position consistency and a lower dose to the bladder. With improved non-target tissue and bladder volume sparing, IMRT is an option for dose escalation. However, this analysis did not find an advantage concerning the integral rectal dose with IMRT versus 3D-CRT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Pinkawa et al . has described decreasing bowel and rectal volumes during the course of treatment from urinary and bowel urgency [6]. Similarly, constipation or urinary retention that resolve or start during the course of treatment could further alter the direction of the forces exerted by the bladder and rectum, and account for some of the pattern changes observed during the course of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pinkawa et al . has described decreasing bowel and rectal volumes during the course of treatment from urinary and bowel urgency [6]. Similarly, constipation or urinary retention that resolve or start during the course of treatment could further alter the direction of the forces exerted by the bladder and rectum, and account for some of the pattern changes observed during the course of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It has been utilized for the salvage or adjuvant treatment of post-prostatectomy patients [5-7]. Compared to three-dimensional conformal radiotherapy (3D-CRT), IMRT has the capacity of lowering the dose to the bladder especially when it is full [6]. IMRT can also reduce the dose to the rectum compared to 3D-CRT [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…head and neck [48], lung [49], breast [50], prostate [32,51,52] or other [53]. For radiotherapy of glioblastomas the feasibility and efficacy of IMRT planning with a simultaneous boost could be shown by Chan et al [54].…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors have reported that the PB moves independently of bony anatomy, [15][16][17][18][19] and in a number of these studies CBCT scans were used to assess this movement. 10,20,21 This has implications for daily image guidance techniques applied during radiotherapy treatment in post-prostatectomy patients.…”
Section: Discussionmentioning
confidence: 99%